2009
DOI: 10.1056/nejmoa0810780
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Importance of Brown Adipose Tissue in Adult Humans

Abstract: BACKGROUND Obesity results from an imbalance between energy intake and expenditure. In rodents and newborn humans, brown adipose tissue helps regulate energy expenditure by thermogenesis mediated by the expression of uncoupling protein 1 (UCP1), but brown adipose tissue has been considered to have no physiologic relevance in adult humans. METHODS We analyzed 3640 consecutive 18F-fluorodeoxyglucose (18F-FDG) positron-emission tomographic and computed tomographic (PET–CT) scans performed for various diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

115
3,221
19
58

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,788 publications
(3,511 citation statements)
references
References 33 publications
115
3,221
19
58
Order By: Relevance
“…It has been proposed that beige adipocytes can derive from a distinct precursor and display a gene expression pattern different from that of brown adipocytes 9. Recent studies also reported the presence of BAT and the formation of UCP1‐expressing adipocytes within WAT depots in adult humans 10, 11. In humans, UCP1‐positive adipocytes exhibiting both brown12, 13, 14 and beige13, 14, 15, 16 molecular signatures have been described.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that beige adipocytes can derive from a distinct precursor and display a gene expression pattern different from that of brown adipocytes 9. Recent studies also reported the presence of BAT and the formation of UCP1‐expressing adipocytes within WAT depots in adult humans 10, 11. In humans, UCP1‐positive adipocytes exhibiting both brown12, 13, 14 and beige13, 14, 15, 16 molecular signatures have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Visceral WAT accumulates with advancing age in men and women (Weisberg et al 2003;Ortega et al 2008;Gavi et al 2007), and inflammatory processes within visceral WAT place the elderly at increased risk for metabolic syndrome, diabetes, and cardiovascular disease (Trayhurn and Beattie 2001;Trayhurn 2005;Cartwright et al 2007;Huffman and Barzilai 2009). Recent evidence indicates that thermogenic brown fat decreases with age and this change contributes to obesity (Nedergaard et al 2007;Cypess et al 2009;van Marken Lichtenbelt et al 2009;Virtanen et al 2009). Furthermore, biological aging is associated with increased bone marrow adipogenesis, an etiologic factor underlying osteopenia and osteoporosis (Meunier et al 1971;Gimble et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…1 Obesity is defined by the expansion of white adipose tissue (WAT), but recent evidence suggests that the adult human body also contains functionally distinct, brown adipose tissue. [2][3][4][5][6][7][8] In contrast to WAT, which has a primary role in energy storage, brown adipose tissue specializes in energy dissipation as heat (Cannon and Nedergaard 9 ). This thermogenic property of brown fat results from its high content of mitochondria, cell organelles where energy dissipation occurs.…”
Section: Introductionmentioning
confidence: 99%